Terapi Bermain Puzzle untuk Meningkatkan Fungsi Kognitif Lansia - Wahyuningsih, Tri; Aryanti, Dita (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The increase in life expectancy is accompanied by an increase in the number of elderly people. Decreased cognitive function is a problem faced by the elderly. Efforts that can be made to maintain cognitive function are through increasing activities that stimulate the brain. Puzzle therapy is one of the non-pharmacological therapies to stimulate cognitive function and slow the onset of dementia. This study aimed to determine the benefits of applying puzzle play therapy to the cognitive level of the elderly. This study was a case report on an elderly person who was given puzzle therapy, then cognitive function measurements were carried out using a cognitive function level measurement instrument (MMSE). Measurements were taken in the phases before and after the provision of puzzle play therapy. Then a descriptive comparative analysis was carried out and presented textularly. The results of the analysis showed that there was a change in the MMSE score in the elderly from 21 to 27. Furthermore, it was concluded that descriptively, puzzle play therapy can improve the cognitive function of the elderly. It is hoped that puzzle therapy can provide information to the wider community to overcome the problem of independence of the elderly who experience decreased cognitive function.Keywords: elderly; cognitive function; puzzle play therapy ABSTRAK Peningkatan usia harapan hidup dibarengi dengan peningkatan jumlah penduduk lanjut usia. Penurunan fungsi kognitif merupakan masalah yang dihadapi lansia. Upaya yang dapat dilakukan untuk mempertahankan fungsi kognitif adalah melalui peningkatan aktivitas yang menstimulasi otak. Terapi puzzle  merupakan salah satu terapi non farmakologi untuk merangsang fungsi kognitif dan memperlambat terjadinya onset demensia. Studi ini bertujuan untuk mengetahui manfaat penerapan terapi bermain puzzle terhadap tingkat kognitif lansia. Studi ini merupakan laporan kasus pada seorang lansia yang diberikan terapi puzzle, lalu dilakukan pengukuran fungsi kognitif menggunakan instrumen pengukuran tingkat fungsi kognitif (MMSE). Pengukuran dilakukan pada fase sebelum dan sesudah pemberian terapi bermain puzzle. Lalu dilakukan analisis perbandingan secara deskriptif dan disajikan secara tektular. Hasil analisis menunjukkan bahwa terjadi perubahan skor MMSE pada lansia dari 21 menjadi 27. Selanjutnya disimpulkan bahwa secara deskriptif, terapi bermain puzzle dapat meningkatkan fungsi kognitif lansia. Diharapkan terapi puzzle dapat informasi kepada masyarakat luas untuk mengatasi masalah kemandirian lansia yang mengalami penurunan fungsi kognitif.Kata kunci: lansia; fungsi kognitif; terapi bermain puzzle